O-183 Frequent spontaneous abortion in pregnancies followed by ICSI using frozen sperm from patients with testicular germ cell tumor (TGCT). (30th June 2022) - Hamada, H; Hayama, T; Ijuin, A; Miyakoshi, A; Yamamoto, M; Ueno, H; Saito, M; Tochihara, S; Takeshima, T; Tanoshima, M; Takeshima, K; Sakakibara, H; et al.
Abstract: Study question: Despite the high rate of sperm chromosome abnormalities in testicular germ cell tumor (TGCT), why is newborn aneuploidy rate in pregnancies with TGCT patient normal? Summary answer: Miscarriage rate is higher in the pregnancy of TGCT patients than of non-TGCT cancer patients, although the pregnancy rate in ICSI was not significantly different. What is known already: Previous reports showed higher sperm aneuploidy in TGCT patients than control males. The sperm aneuploidy rate is high before treatment, and after radical treatments peaked at 6 months after treatment and remained high until 24 months after treatment. However, in the Swedish government base study, the rate of newborn malformations including aneuploidy in all pregnancy with TGCT patients was higher than without TGCT, but not statistically significant. In only natural pregnancies, the rate was not significantly different between the two groups. The cause for discrepancy within sperm aneuploidy and newborn aneuploidy was not well clarified. Study design, size, duration: To clarify the mechanism for the purifying selection of aneuploid sperm in conception, we examined ICSI cases with TGCT patients that did not include natural sperm competition and compared to controls with non-TGCT cancer patient, who have normal rate of aneuploid sperm. By investigating ICSI outcomes, we aimed to determine which stage of embryonic development are affected by the sperm of TGCT patients. Participants/materials, setting, methods: Under ethical review of Yokohama city university, the 10 TGCT patients (123 oocytes) and 16 non-TGCT cancer patients (251 oocytes) who underwent ICSI with their frozen sperm from 2012 to 2021 were enrolled. Fertilization, embryo viability and embryo transfer outcomes (pregnancy and miscarriage rate) were examined between two groups underwent ICSI with cryopreserved sperm for fertility preservation. Clinical information was retrospectively collected from medical records. Main results and the role of chance: The patients' age of sperm cryopreservation was 21-56 years old. 10 cases of TGCT were diagnosed as seminoma (3), non seminoma (6), and unknown (2). 15 cases of non-TGCT were diagnosed as malignant blood diseases (9), prostate cancer (2), bladder cancer (1), and others (3). In both groups, all patients were treated by ICSI with cryopreserved sperm obtained prior to chemotherapy. The mean age of female partners in TGCT was 33.2±3.5 years and not different with 35.8±3.4 years in non-TGCT meaning no different age factor. The fertilization rate, viable embryo rate, pregnancy rate and chemical abortion rate of TGCT vs non-TGCT group were 76.4% vs 67.7%, 64.3% vs 61.7%, 37.1% vs 21.7%, 7.1% vs 23.1%, respectively. Those developmental evaluations were not significantly different between two groups. However, spontaneous abortion rate was significantly higher 46.2% in TGCT group than 10% in non-TGCT group (p < 0.05). Further, in our follow-up, no congenital malformations in the babies born in either group (5 babies in TGCT vs 7 babies in non-TGCT group). The outcome of ICSI using sperm in TGCT patients show normal pregnancy rate but include higher spontaneous abortions rate, suggesting aneuploid embryo were negatively purifying selected under post-implantation stage. Limitations, reasons for caution: Because ICSI with fertility-preserving frozen sperm in TGCT patient is rare even in reproduction center in general university hospital, single center analysis is still small and limited. More case reports and studies for TGCT fertility preservation are needed for more accurate evaluation. Wider implications of the findings: In TGCT patients, chromosome aberrations and DNA fragmentation of sperm may not be apparent in natural pregnancies with normal sperm competition, but may become apparent as spontaneous abortions when ICSI were performed, suggesting PGT-A can predict and avoid the hidden risk of repeated pregnancy loss in ICSI to TGCT patients. Trial registration number: not applicable